2019
DOI: 10.1002/marc.201900572
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsically Microporous Polymer Nanosheets for High‐Performance Gas Separation Membranes

Abstract: Microporous polymer nanosheets with thicknesses in the range 3–5 nm and with high apparent surface area (Brunauer–Emmett–Teller surface area 940 m2 g−1) are formed when the effectively bifunctional (tetrafluoro) monomer used in the preparation of the prototypical polymer of intrinsic microporosity PIM‐1 is replaced with an effectively tetrafunctional (octafluoro) monomer to give a tightly crosslinked network structure. When employed as a filler in mixed‐matrix membranes based on PIM‐1, a low loading of 0.5 wt%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 36 publications
1
23
1
Order By: Relevance
“…Many small structures are visible, along with some ribbon-like features that may arise from agglomeration of smaller species. This is in marked contrast to the high cross-link density network-PIM-1 previously reported, 34 which showed nanosheets with thicknesses in the range 3−5 nm and lateral dimensions of a few hundred nanometers. For the LCD-network-PIM-1, height profiles are shown in Figure 4(c) along lines passing through some of the small particles, indicated as lines 1−4 in Figure 4(b).…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…Many small structures are visible, along with some ribbon-like features that may arise from agglomeration of smaller species. This is in marked contrast to the high cross-link density network-PIM-1 previously reported, 34 which showed nanosheets with thicknesses in the range 3−5 nm and lateral dimensions of a few hundred nanometers. For the LCD-network-PIM-1, height profiles are shown in Figure 4(c) along lines passing through some of the small particles, indicated as lines 1−4 in Figure 4(b).…”
Section: Resultscontrasting
confidence: 99%
“…Mixed gas permeability measurements were carried out using a binary feed mixture (25 mL min −1 of each gas) in a permeation apparatus based on the standard variable volume method, as reported previously. 34 The feed side pressure was kept constant at approximately 3 bar and 25 °C and the permeate side was at atmospheric pressure. Pieces of prepared freestanding membranes were masked between two aluminum-tape donuts, and the membrane−aluminum interface was sealed using twopart potting epoxy (Araldite Rapid, Industrial MTCE Suppliers).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The group also [200] used a highly crosslinked nanosheet form of network-PIM-1 as the filler in a more linear PIM-1. The authors demonstrated that the network-PIM-1 nanosheets (ABET = 940 m 2 ·g -1 ), produced by using tetra-functional (octafluoro) monomer instead of the typical bi-functional (tetrafluoro) monomer, when incorporated into PIM-1 (Mw = 158,000 g·mol -1 ; Đ = 3.0, ABET = 780 m 2 ·g -1 ) positively changed the membrane performance.…”
Section: Network Pimsmentioning
confidence: 99%
“…Mixing superglassy polymers with porous and non-porous fillers has proven an attractive route to overcome the physical aging. Freestanding mixed matrix membranes (MMMs) have been successfully fabricated with metal organic framework (MOFs) [ 20 , 21 ], zeolites [ 22 ], silica [ 23 ], graphene-based materials [ 24 , 25 ], porous aromatic frameworks (PAFs) [ 26 , 27 ], and hypercrosslinked polymers (HCPs) [ 28 , 29 , 30 , 31 ]. The feasibility of using superglassy polymers in the hybrid membrane/amine process mainly depends on the long-term performance of the polymers under industrial operating condition, when produced as thin films to maximize CO 2 permeance.…”
Section: Introductionmentioning
confidence: 99%